Multiorganelle Localization of Metallated Phthalocyanine Photosensitizer in Colorectal Cancer Cells (DLD-1 and CaCo-2) Enhances Efficacy of Photodynamic Therapy - Palesa Rose Sekhejane; Nicolette Nadene Houreld; Heidi Abrahamse (International Journal of Photoenergy)
Colorectal cancer is the third most commonly diagnosed cancer. Amongst treatments that have been explored, photodynamic therapy (PDT) is a treatment that is of interest as it poses ideal advantages such as affinity for cancer cells. This study aimed to determine the correlation between the localization site of a sulfonated zinc phthalocyanine (ZnPcSmix) photosensitizer (PS) and its associated cell death pathway in vitro in colorectal cancer cell lines (DLD-1 and CaCo-2). Visible morphological changes were observed in PDT treated cells after 24 h. Reactive oxygen species (ROS) were detected and visualized 1 h after PDT. ZnPcSmix was predominantly localized in lysosomes and partially in the mitochondria. FITC Annexin V staining showed a significant decrease in the percentage of viable DLD-1 and CaCo-2 cells 24 h after PDT, with an increase in apoptotic cell population. Moreover, there was a significant increase in both cathepsin D and cytochrome C at 1 and 24 h. In conclusion, ZnPcSmix showed the ability of inducing apoptotic cell death features in PDT treated cells.